2003
DOI: 10.1177/001440290306900405
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Inclusion on Language Development and Social Competerne among Preschoolers with Disabilities

Abstract: This article describes progress in language development and social competence among 96 preschoolers with disabilities in inclusive and segregated classes. Pretest ability was the strongest predictor of progress. Other child, parent, and family characteristics were not associated with pretest developmental abilities or with progress. Degree of disability did not moderate the impact of placement type on developmental outcomes, controlling for pretest ability. Effect sizes, however, indicated thatposttest scores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 24 publications
4
52
0
3
Order By: Relevance
“…A small number of studies have considered the link between inclusivity and key child outcomes, such as academic achievement or social skills. Most of these studies focus on younger children [3][4][5][6][7][8] ; fewer have assessed the experiences of adolescents. 9,10 (For a review of this literature, see Ferraioli and Harris.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of studies have considered the link between inclusivity and key child outcomes, such as academic achievement or social skills. Most of these studies focus on younger children [3][4][5][6][7][8] ; fewer have assessed the experiences of adolescents. 9,10 (For a review of this literature, see Ferraioli and Harris.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several studies have examined the effectiveness of inclusive education on academic achievement and focused on several indicators of socio-emotional and behavioral functioning such as the self-concept, social skills, peer relationships, social status, and problem behaviors of SEN students. A number of studies have reported that inclusive education yielded positive outcomes for SEN students in terms of communication skills, social skills, and behavior (For a review, see Katz & Mirenda, 2002; see also Rafferty, Piscitelli, & Boettcher, 2003). However, other studies have indicated that inclusive education was not effective in obtaining positive outcomes for SEN students (Freeman & Alkin, 2000;Gresham & McMillian, 1997).…”
mentioning
confidence: 99%
“…Inclusion in general education provides students with disabilities access to both academic and social opportunities that are generally not available in segregated settings (Downing & Eichinger, 2008). The general education classroom offers students with disabilities access to the core curriculum (Soukup, Wehmeyer, Bashinski, & Bovaird, 2007), greater opportunities for growth in communication and social interaction (Rafferty, Piscitelli, & Boettcher, 2003), and the benefit of typically developing peers modeling age-appropriate behavior (Carter & Kennedy, 2006). Further, research has shown that students without disabilities benefit from the inclusion of students with disabilities in their classes as well (Downing & Peckham-Hardin, 2007;Katz & Mirenda, 2002).…”
Section: Rationale For Inclusive Catholic Educationmentioning
confidence: 99%